2002
DOI: 10.1021/ja0122391
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Mechanism of Heme Oxygenase through EPR and ENDOR of Cryoreduced Oxy-Heme Oxygenase and Its Asp 140 Mutants

Abstract: Heme oxygenase (HO) catalyzes the O(2)- and NADPH-cytochrome P450 reductase-dependent conversion of heme to biliverdin, Fe, and CO through a process in which the heme participates both as a prosthetic group and as a substrate. In the present study, we have generated a detailed reaction cycle for the first monooxygenation step of HO catalysis, conversion of the heme to alpha-meso-hydroxyheme. We employed EPR (using both (16)O(2) and (17)O(2)) and (1)H, (14)N ENDOR spectroscopies to characterize the intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
277
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(294 citation statements)
references
References 34 publications
(105 reference statements)
16
277
0
Order By: Relevance
“…DISCUSSION HmuO, like HO-1, yields only the ␣-isomer of biliverdin (12). Regioselectivity of HO catalysis is defined at the first oxygenation step (50), where the remote hydroperoxo oxygen attacks the porphyrin ␣-meso-carbon to form ␣-meso-hydroxyheme (6,25). Previous studies have suggested that regiospecific degradation of heme by HO activity is primarily under the steric control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DISCUSSION HmuO, like HO-1, yields only the ␣-isomer of biliverdin (12). Regioselectivity of HO catalysis is defined at the first oxygenation step (50), where the remote hydroperoxo oxygen attacks the porphyrin ␣-meso-carbon to form ␣-meso-hydroxyheme (6,25). Previous studies have suggested that regiospecific degradation of heme by HO activity is primarily under the steric control.…”
Section: Resultsmentioning
confidence: 99%
“…3). Asp-136, which is equivalent to the catalytically critical Asp-140 of HO-1 (25,48,49), stabilizes Wat1 and Wat2. Wat2 is connected by Wat3 and Wat4 to the side chain of Gln-46, which, in turn, is connected by another water molecule to the surface amino acid, Asp-86.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cpd I has an EPR signal at g= 2, whereas Cpd II is EPR silent [28,29]. For PGIS, approximate 16% of the low-spin heme signals were retained upon reaction with 15-HPETE (solid line vs. dotted line in Fig.…”
Section: Eprmentioning
confidence: 95%